PROGRAM EVALUTAION OF ENGLISH CLUB USING CIPP MODEL IN PRIMARY SCHOOL - Berkat Christin Manurung; Muchlas Suseno (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
Crystal, D. (2003). English as a global language. (2nd ed. First ed,1997), Cambridge: Cambridge University Press. XV + 212 pp., ISBN Hb 0521 82347 1, Pb 0 521 53032 6.Fitzpatrick, Jody, L., James R. Sanders, Blaine R. Worthen. (2004). Program Evaluation: Analitycal Approach and Practical Guidelines. Boston, Pearson Education, Inc.Kilickaya, F. (2009). World Englishes, English as an international language and applied linguistics. English Language Teaching, 2 (3), 35-38.Marinova-Todd, S., D. Marshall, and C. Snow. 2000. Three misconceptions about age and L2 learning. TESOL Quarterly, 34 (1): 9–34.Paltridge, B. (2001). Genre and the Language learning classroom. Michigan: University of Michigan Press.Putra, E. (2020). The Importance of Learning English Nowadays. Sepuluh Nopember Institute of Technology (ITS): Surabaya.Salahudin, Anas. (2010). Bimbingan dan Konseling. Bandung: Pustaka Setia.Stufflebeam, D. L., Zhang, G. (2017). The CIPP evaluation model: How to evaluate for improvement and accountability. Guilford Publications.Stufflebeam, D. L. (2003). The CIPP Model for evaluation. Presented at the Annual Conference of the Oregon Program Evaluators Network (OPEN), Portland, Oregon. Retrieved from http://link.springer.com/chapter/10.1007/978-94-010-0309-4_4